Mass ringing of flightless Blue and Lesser Snow Geese in Canada's eastern Arctic - Cooch, Graham (Wildfowl, 1956)
The capture of large numbers of moulting adult Snow Geese and their goslings on Southampton Island is described. The method of capture, adapted from a long-established Eskimo technique, resembles that used for catching flightless Pink-footed Geese in Iceland. In the three summers 1952-54, 15,000 geese were ringed on Southampton Island and at a colony at Eskimo Point, North-West Territory. Over 10% have already been recovered. These recoveries, and live recaptures, have provided much information on the migration pattern of the species, on the areas in which these populations are most heavily shot, and on the extent of return to the breeding colony in succeeding years. The third known colony of the species is on Baffin Island. It is hoped to ring geese there in the summer of 1958. The ringing programme will make possible detailed studies of the population structure. Preliminary calculations suggest many similarities between the structure of the Snow Geese population and that of the Pink-footed Goose. The number of Blue and Lesser Snow Geese (Anser caerulescens), breeding in the eastern Canadian Arctic exceeds 800,000, of which about 350,000 are Blue Geese.